Effectiveness of Notary Supervision by The Notary Supervision Council to Prevent Malpractice in Carrying Out Notary Practice in Banyumas Regency - Faddil, Zainulloh; Sri Darmadi, Nanang; Djunaedi, Djunaedi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
This study aims to analyze in depth the effectiveness of supervision carried out by the Notary Supervisory Board (MPN) in Banyumas Regency to prevent malpractice in carrying out notary duties. The main problem studied is how the MPN's supervision is implemented in Banyumas Regency and what factors hinder the effectiveness of such supervision, both from internal and external aspects. The research method used is empirical juridical with a sociological legal approach. The research location was determined in Banyumas Regency, involving informants from the Regional Supervisory Board (MPD) and notary practitioners. The results of the study indicate that supervision has not reached the optimal level of effectiveness as mandated by the Notary Law (UUJN). The main obstacles include limited human resources, minimal operational budget allocation, and psychological obstacles in the form of excessive corps solidarity (ewuh-pakewuh) among fellow notaries. Philosophically-theologically, this supervisory function is a manifestation of the Hisbah concept in Islamic law, where the MPN acts as Muhtasib to ensure that the notary as Al-Katib carries out his duties honestly, transparently and responsibly for the benefit of the people.